Rheumatic Heart Disease in Kerala: A Vanishing Entity? An Echo Doppler Study in 5–15-Years-Old School Children. (14th September 2015) - Nair, Bigesh; Viswanathan, Sunitha; Koshy, A. George; Gupta, Prabha Nini; Nair, Namita; Thakkar, Ashok
Abstract : Background. Early detection of subclinical rheumatic heart disease by use of echocardiography warrants timely implementation of secondary antibiotic prophylaxis and thereby prevents or retards its related complications. Objectives. The objective of this epidemiological study was to determine prevalence of RHD by echocardiography using World Heart Federation criteria in randomly selected school children of Trivandrum. Methods. This was a population-based cross-sectional screening study carried out in Trivandrum. A total of 2060 school children, 5–15 years, were randomly selected from five government and two private (aided) schools. All enrolled children were screened for RHD according to standard clinical and WHF criteria of echocardiography. Results. Echocardiographic examinations confirmed RHD in 5 children out of 146 clinically suspected cases. Thus, clinical prevalence was found to be 2.4 per 1000. According to WHF criteria of echocardiography, 12 children (12/2060) were diagnosed with RHD corresponding to echocardiographic prevalence of 5.83 cases per 1000. As per criteria, 6 children were diagnosed with definite RHD and 6 with borderline RHD. Conclusions. The results of the current study demonstrate that echocardiography is more sensitive and feasible in detecting clinically silent RHD. Our study, the largest school survey of south India till date, points towards declining prevalence of RHD (5.83/1000 cases) using WHF criteria in Kerala.